Pelatihan English Communication Skills dalam Menghadapi Era 4.0 pada Remaja di RPTRA Kalideres, Jakarta Barat - Rizky Mirani Desi Pratama; Dwi Puji Hastuti; Fadilah Fadilah; Dina Purnamasari (Jurnal Abdimas Komunikasi dan Bahasa, 2023)
Child-Friendly Open Public Space (RPTRA) Kalideres, West Jakarta is an economically/socially non-productive partner. The lack of ability to speak English properly and correctly is one of the main problems faced by high school students around RPTRA Kalideres. One of the difficult English skills for high school students around RPTRA Kalideres is the ability to communicate in English. What is often experienced by high school students around RPTRA Kalideres is wanting to say something in English but don't know what vocabulary to use and are afraid or not used to using English as a medium of communication. This is the background for lecturers in the English Study Program to hold community service activities. This form of community service is carried out in community service which is divided into two, namely the presentation of theory and the practice of communicating in English (speaking and writing). The media used in the English training this time are pictures and videos. After receiving material on how to communicate in English, the participants will immediately practice speaking and writing in English. The participants will be given a theme and must explain the theme in English both orally and in writing. It is hoped that with this training, participants can master English as one of the basic assets to be able to compete in facing the global era and can open various opportunities to achieve success.